Influence Return on Equity (ROE), and Net Profit Margin (NPM) Against Return Shares of Food and Beverage Sub-Sector Companies on the Indonesian Stock Exchange Period 2022-2023 - Joni Devitra (Publikasi Indonesia, 2025)
Focusing on the 2022–2023 period, this research investigates the effect of